إشكالية تحريف عبدالله بن سعد ابن أبي سرح للنص القرآني في ضوء كتب التفسير: دراسة تحليلية نقدية ‘Abd Allah ibn Saad ibn Abi Sarh’s Distortion of the Qur’anic Text in the light of Tafsir Literature: A Critical Analysis - اسبينداري, عبدالرّحمن عمر (Journal of Islam in Asia (E-ISSN 2289-8077), 2015)
الملخّص يهدف هذا البحث إلى دراسة إشكالية تحريف الصحابي عبدالله بن سعد ابن أبي سرح للنص القرآني بينما كان كاتبًا للوحي في ضوء كتب التفسير، وقد اتبع الباحث المنهج التاريخي القائم على النقد والتحليل، من خلال دراسة وتحليل الروايات والأخبار التي وردت في هذه المسألة في أغلب كتب التفسير، فضلًا عن اتباع منهج علماء الجرح والتعديل في دراسة الأسانيد والحكم عليها. وقد خرج البحث بجملة نتائج، يمكن إجمالها بما يأتي: نقل أغلب المفسرين روايات تؤكد قيام ابن أبي سرح بتحريف النص القرآني دون تفنيد أو تحقيق، بل تجاوز الأمر ذلك إلى إدعاء أن ذلك قد وقع بموافقة الرسول صلى الله عليه وسلم، والأغرب من ذلك أن أغلبهم قد تعامل معها وكأنها صحيحة، وبنى عليها نتائج خطيرة وعلى رأسهم الطبري، مع أن ضعفها واضح. ومنها: أن ما قاله المفسرون من نزول عدد من الآيات فيه ولا سيما من الأنعام والنحل والأنفال أو غيرها يخالف السياق العام لتلك الآيات، إذ يتضح أن ما ذكر في السياق لا ينطبق على شخص مثل ابن أبي سرح كونه تاب ورجع إلى الإسلام، فضلًا عن ضعفها. ومنها: نقل مفسرون معاصرون هذه الروايات والأخبار الساقطة مثل الشعرواي وسيد قطب وسعيد حوى وغيرهم، في حين ردها آخرون أمثال محمد عزة دروزة ومحمد رشيد رضا وابن عاشور. الكلمات المفتاحية: إشكالية، تحريف، عبدالله بن سعد ابن أبي سرح، النص القرآني، كتب التفسير. Abstract This research focuses, in the light of tafsÊr literature, on the distortion of the companion ‘Abd Allah ibn Sa‘d ibn AbÊ SarÍ of the Qur’anic text despite him being a scribe of the Revelation. Based on historical criticism and analysis, we examine the reports and narrations on this issue as available in many tafsÊr works, by applying the methods of scholars in the science of al-jarÍ wa al-taʿdīl. The study reached numerous conclusions. Some of them are: Most Qur’anic commentators recorded reports of Ibn AbÊ SarÍ’s distortion of the Qur’anic text without proper investigation into their authenticity. Some even suggested that the distortion was God Forbid consented by the Prophet (s.a.w.) himself. What is strange is that many of the commentators considered such reports authentic and came up with dangerous conclusions. The most prominent among these commentators is al-ÙabarÊ. These suggestions and reports are not free from deficiencies. The suggested distortions violate the overall contextual flow of the verses from SËrah al-Anʿām, SËrah al-Naḥl, SËrah al-Anfāl. It was not possible on the part of a Companion, Ibn AbÊ SarÍ who had repented and returned to Islam to effect such distortions in the Qur’anic text. Some contemporary Qur’anic commentators like al-Sha‘rāwī, Sayyid QuÏb, and Sa‘Êd ×awwa have reported such rejected claims, whilst others such as Muhammad ‘Izzat Darwazah, Muhammad RashÊd RiÌÉ, and Ibn ‘ÓshËr have rejected them as unreliable. Keywords: Distortion, ‘Abd Allah ibn Sa‘d ibn AbÊ SarÍ, the Qur’anic Text, TafsÊr Literature.